1931
DOI: 10.1098/rspa.1931.0069
|View full text |Cite
|
Sign up to set email alerts
|

On periodicity in series of related terms

Abstract: An important extension of our ideas regarding periodicity was made in 1927 when Yule* pointed out that, instead of regarding a series of annual sunspot numbers as consisting merely of a harmonic series to which a series of random terms were added, we might suppose a certain amount of causal relationship between the successive annual numbers. In that case the system might be regarded as a physical system possessing one or more natural oscilla tions of its own, all subject to damping ; and the effect of annual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…The earliest discussed estimator is the r 1 estimator (Walker 1931), as implemented in the Yule–Walker model (Yule 1927; Box and Jenkins 1976). However, since several studies have found that the bias of r 1 for small samples is large, especially for data with a positive autocorrelation, various alternatives were proposed (Huitema and McKean 1991, 1994; DeCarlo and Tryon 1993; Arnau and Bono 2001; Solanas et al.…”
Section: Selection Of Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest discussed estimator is the r 1 estimator (Walker 1931), as implemented in the Yule–Walker model (Yule 1927; Box and Jenkins 1976). However, since several studies have found that the bias of r 1 for small samples is large, especially for data with a positive autocorrelation, various alternatives were proposed (Huitema and McKean 1991, 1994; DeCarlo and Tryon 1993; Arnau and Bono 2001; Solanas et al.…”
Section: Selection Of Estimation Methodsmentioning
confidence: 99%
“…Several estimation methods have been proposed to estimate the AR(1) model. These estimation methods include closed form estimation methods, such as the r 1 estimator (Yule 1927; Walker 1931; Box and Jenkins 1976), C-statistic (Young 1941) and Ordinary Least Squares (OLS) estimator, and iterative estimation methods, such as frequentist Maximum Likelihood Estimation (MLE) and Bayesian Markov Chain Monte Carlo (MCMC) estimation. The performance of the closed form estimation methods in terms of efficiency have been examined and compared in some simulation studies (Huitema and McKean 1991; DeCarlo and Tryon 1993; Arnau and Bono 2001; Solanas et al.…”
Section: Introductionmentioning
confidence: 99%
“…Equation 3.1 can be expanded as a Yule-Walker equation (Yule, 1927;Walker, 1931; Boashash, 1995; Kadtke & Kremliovsky, 1999), xτ=axτ2. Applying the expectation operator false〈Ffalse(tfalse)false〉limTfalse(1T0TFfalse(tfalse)normaldnormaltfalse), we get a=false〈xτfalse〉false〈xτ2false〉=false〈xτfalse〉false〈x2false〉. For a harmonic signal with one frequency (this is a special solution of the linear DDE in equation 3.1; see Falbo, 1995, for details), x ( t ) = A cos(ω t + φ).…”
Section: Functional Embedding As a Connection Between Nonlinear Dynmentioning
confidence: 99%
“…In this AR model, the curve of the time series was fit by the linear combination of the observed historical values. Walker developed the MA model based on the AR model in 1931 [10]. The MA model used a linear combination of historical random disturbances and prediction errors to obtain the current predictive value.…”
Section: Introductionmentioning
confidence: 99%